Liquidus Temperature Measurements for the BaCl2-NaCl and MgCl3-NaCl Systems (using novel in-situ probe) - Yan, X.Y.; Li, N.; Grimsey, Eric (AusIMM, 1996)
A technique has been developed for the fast measurement of the liquidus temperature of molten salt systems. The method employs a type K thermocouple embedded within the centre of a copper cylinder. The cylinder is immersed into the molten salt bath and the resultant heating curve is recorded using a PC-based data logging system. Upon immersion of the cylinder into the bath, a layer of salt freezes from the melt onto the surface. When this layer remelts during heating, the shape of the heating curve exhibits a change. The onset of this change can be detected by numerical differentiation of the heating curve, and the temperature at the onset represents an estimate of the liquidus of the melt. This work describes the technique and its application to the measurement of liquidus temperatures of MgCl2-NaCl and BaCl2-NaCl salt mixtures, in addition to a number of solidus temperatures.